Deconstructing Creativity and Designing Dakwah Tasks: Problem Solving Learning in Madrasah Ibtidaiyah - Didit Darmawan; Alfi Nadiroh NF (Civiliza Publishing, Indonesia., 2026)
This study aims to analyze conceptually the relationship between freedom of expression in madrasah and the development of problem solving skills in elementary school children, as well as examining the design of creative tasks containing dakwah values to increase student learning interest. This qualitative literature study traces various scientific sources discussing creativity, freedom of expression, problem solving, and integration of Islamic values in primary education. Data were analyzed using content analysis method with reference to the thoughts of educational experts. The findings show that freedom of expression provides space for children to develop cognitive flexibility, courage to try, and resilience in facing difficulties which are the main capital for problem solving skills. A madrasah environment that supports expression creates a psychological safety that allows children to see problems from multiple perspectives. On the other hand, creative tasks designed according to the developmental stage of children and containing dakwah messages succeed in making religious learning relevant and enjoyable. Integration of Islamic values in drawing, storytelling, role playing and art projects increases students' intrinsic motivation to learn. This study implies the need for a paradigm shift in madrasah learning towards a student-centered approach and continuous training for teachers. Further empirical research is needed to test the effectiveness of this conceptual model.